The Influence Of The Use Of E-Learning On Student Achievement Index In The Pandemic Period (Case Study On Students Of The Faculty Of Economics And Business, University Of Muhammadiyah Surakarta) - Putri, Fatwasari Soeratno (Prosiding University Research Colloquium, 2021)
The COVID-19 pandemic has had a major impact on all sectors, one of them is theeducation sector. It has been more than a year that students and college students havebeen learning with online or virtual learning systems using technology or often known ase-learning. This study discusses the effect of using e-learning on the achievement index ofFEB UMS students during the pandemic. This research method is a quantitative methodusing purposive sampling technique, data collection is done online by distributingquestionnaires in the form of a google form link to respondents. The analysis used in thisstudy using multiple linear regression analysis. The results showed that the e-learningvariable significantly affected the student achievement index.